2020
DOI: 10.21203/rs.3.rs-72845/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genotoxic Impact of Aluminum-containing Nanomaterials in Human Intestinal and Hepatic Cells.

Abstract: Background: Exposure of consumers to aluminum-containing nanomaterials (Al NMs) through numerous products is an area of concern for public health agencies since human health risks are not completely elucidated. In addition, the available data on the genotoxicity of Al2O3 and Al0 NMs are inconclusive or rare. In order to provide further information, the present study investigated the in vitro genotoxic potential of Al0 and Al2O3 NMs in intestinal and liver cell models since these tissues represent organs which … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Most conventional toxicity assays rely on colorimetric/fluorometric principals, and the particular physical properties of NMs mean that they are prone to interfere with testing methods, as shown in several studies (Ong et al, 2014). Possible interference between NMs and the comet assay has been investigated (Kain et al, 2012;Magdolenova et al, 2012;Karlsson et al, 2015;Ferraro et al, 2016;George et al, 2017;Jalili et al, 2022). For instance, Ferraro et al, 2016, showed a possible interaction between naked DNA and NMs just before the electrophoresis step (Ferraro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Most conventional toxicity assays rely on colorimetric/fluorometric principals, and the particular physical properties of NMs mean that they are prone to interfere with testing methods, as shown in several studies (Ong et al, 2014). Possible interference between NMs and the comet assay has been investigated (Kain et al, 2012;Magdolenova et al, 2012;Karlsson et al, 2015;Ferraro et al, 2016;George et al, 2017;Jalili et al, 2022). For instance, Ferraro et al, 2016, showed a possible interaction between naked DNA and NMs just before the electrophoresis step (Ferraro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%